Tailorable Nanoparticles for Magnetic Water Cleaning of Polychlorinated Biphenyls - Müller, Lukas; Zehetmeier, Anna; Höfling, Anna; Gaß, Henrik; Voß, Johannes; Krappmann, Daniel; Rockmann, Linda; Harrer, Elias; Zahn, Dirk; Hirsch, Andreas; Halik, Marcus (Small Methods, 2025)
Anthropogenic persistent organic pollutants pose a pressing threat to the environment and human health. They can be found in water bodies all around the world at low but hazardous concentrations. Typical representatives of this contaminant class are polychlorinated biphenyls (PCBs). Here, nanoparticulate core-shell water cleaning agents are presented, which are able to remove PCBs of various chlorination degrees from water. The core consists of superparamagnetic iron oxide nanoparticles (SPIONs) providing a large surface area that can be tuned via self-assembled monolayers (SAMs) composed of phosphonic acid derivates. This shell binds the pollutants non-covalently enabling facile magnetic water remediation. By employing positively charged or hydrophobic SAMs different PCBs can be preferentially removed. Furthermore, these orthogonal functionalities can be integrated into one SPION system. By combining charged and hydrophobic phosphonic acid derivates in so-called binary SAMs the removal preference can be convoluted, which works just as well in real river water. The cost-efficient availability of the base materials for these tailorable nanoparticles is complemented with recyclability laying the foundation for a sustainable water cleaning proces
Keywords: persistent organic pollutants; polychlorinated biphenyls; self-assembled monolayers; superparamagnetic iron oxide nanoparticles; tailorable adsorption; water remediation